Mycotoxigenic fungi in Portuguese wine regions : fumonisin B2 and ochratoxin A - Calado, Thalita (2011)
Studies were conducted between 2001 and 2003 to evaluate the incidence of ochratoxigenic strains in Portuguese wine-grapes. At that time, the main responsible for ochratoxin A production in grapes were found to be Aspergillus carbonarius with a production mean of 1.13 mg/kg and some strains from the Aspergillus niger aggregate with a production mean of 0.14 mg/kg. At that time also, all the black aspergilli isolates were preserved in glycerol and stored at -80 ºC. Since recently A. niger was reported as a producer of the mycotoxin fumonisin B2, its levels produced by black aspergilli isolates from the Portuguese grapes were investigated. Approximately 29% of A. niger aggregate strains were found to produce it between 0.003–6.0 mg/kg with a mean of 0.66 mg/kg and only 6% produced more than 1 mg/kg. The incidence and distribution of fumonisinogenic strains among five Portuguese wine-regions is also presented and correlated with data of the ochratoxigenic ones.